META-ANALISIS PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT TERHADAP HASIL BELAJAR DI SEKOLAH DASAR - Ririn Mustaqimatul Luthfiyah; Mohammad Taufiq; Muhammad Syamsul Ghufron; Akhwani Akhwani (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
This study aims to describe the use of the Teams Games Tournament learning model towards learning outcomes in elementary schools. The method used in this study is the meta-analysis method. This research begins by formulating the topic to be investigated, then making the formulation of the problem and the purpose of the research, at the next stage collecting relevant articles to collect data. The data was obtained from online journal searches through Google Scholar. The keywords used are "Teams Games Tournament learning model" and "learning outcomes". From the search results there are 10 articles. Data obtained and analyzed again using quantitative methods. Based on the analysis of the Teams Games Tournament learning model with proven to be able to improve student learning outcomes with the significant result after being given treatment that 63.2 compared with the result before give treatment that is equal to 56.21 so thath in increases by 6.99.Keywords: Teams Games Tournament learning model, Learning Outcomes, Elementary School.